Analisis Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3), Di PT. Berca Buana Sakti (Studi Kasus Di Pembangunan SUTT 150 kV Kolaka - Pomala Switching - Pelanggan) - Erickson Muttaqin’t; St Rukaiyah; Nurmadhani Fitri Suyuthi (Movere Journal, 2026)
Analysis of the Implementation of the Occupational Health and Safety Management System (SMK3) in the  PT. Berca Buana Sakti  (Case Study Construction Project of 150 kV. Kolaka - Pomala Switching – Customer) The implementation and supervision of SMK3 referring to the PT. Berca Buana Sakti applicable legal system needs to be carried out as well as possible to provide safety assurance for workers and provide maximum benefits for construction actors and the environment so that the risk of accidents and work safety can be overcome, avoided, or minimized. Overall, efforts to improve the implementation of SMK3 in this project are not only focused on procedural aspects, but also on strengthening the safety culture at all levels of the organization, from top management to field workers. All of these improvement actions aim to create a safer, healthier, and more efficient work environment, as well as to minimize the risk of work accidents and occupational diseases that can occur during the 150 kV SUTT Construction Project.  Knowing and describing the analysis of the implementation of the Occupational Safety and Health Management System (SMK3) in the 150 kV SUTT Construction Project implemented by the company. To find out and describe the factors that cause the implementation of Occupational Safety and Health Management System (SMK3) in the 150 kV SUTT Construction Project to be unfulfilled. To find out and describe the corrective actions/improvements in an effort to fulfill the implementation of Occupational Safety and Health Management System (SMK3) in the 150 kV SUTT Construction Project. Theoretically, this research can deepen the understanding of the implementation of SMK3 in construction projects, especially those with high risks such as the construction of High Voltage Air Lines (SUTT) both ongoing and future. A checklist of SMK3 implementation has been implemented based on 166 audit criteria according to PP No. 50 of 2012, with a fulfillment rate of 98.80% (164 criteria fulfilled and 2 criteria not fulfilled). Several criteria in the implementation of SMK3 have not been fully fulfilled, which hinders the optimization of K3 implementation. Several strategic steps have been formulated to improve the implementation of SMK3 more effectively.